ASYMPTOTIC BEHAVIOR OF MODEL OF PLATE SEMILINEAR WITH DISSIPATION DISTRIBUTED LOCALLY - Pérez Salvatierra, Alfonso (2009)
We evalúate the uniform decay of the energy associated with a model semi lineal plates, with dissipation distributed locally, using the principle of continuation single result studied by Ruiz [9] and applied to work with locallydistributed by Zuazua dissipation [10].